Khulu’ sebagai Tindak Pidana Kekerasan dalam Rumah Tangga: Analisis Perspektif Hukum Islam dan Hukum Positif di Indonesia - Hilmy, Reihan Muhammad; Anwar, Syahrul (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This study aims to analyze the relationship between the practice of khulu’ and the potential emergence of domestic violence (KDRT) as a criminal act from the perspective of Islamic law and positive law in Indonesia. The phenomenon of khulu’ frequently arises as a consequence of domestic violence, whether physical or psychological, which drives a wife to seek divorce by offering compensation to her husband. In Islamic law, khulu’ constitutes a woman’s right to free herself from a marital bond by returning the dowry or a certain amount of property to her husband. However, in positive law, acts of violence underlying such a case may be categorized as criminal offenses under Law Number 23 of 2004 concerning the Elimination of Domestic Violence. Therefore, examining the relationship between khulu’ and domestic violence is crucial to understanding the correlation between religious norms and legal norms in protecting women’s rights.